Transient Presyncope Secondary to Posterior Descending Artery Occlusion - Andrew D. Moffat; Jamal T. Al-Khatib; Jennifer Michael; Vien X. Nguyen (Case Reports in Cardiology)
We describe the case of a 64-year-old male initially presenting with presyncope and bradycardia, without any anginal symptoms or objective evidence of myocardial ischemia. A stress test induced no physical symptoms but revealed a left bundle branch block with multiple preventricular contractions on electrocardiogram. Subsequent catheterization revealed severe obstructive disease throughout the coronary arteries. He was treated percutaneously on two separate heart catheterizations. The presyncope and bradycardia resolved after reperfusion of the posterior descending artery.